The Study of Speaker Recognition Technology to Develop a Secure Biometric Authentication Platform for RTAF - Sirinam, Payap; Praneetpolgrang, Prasong (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2022)
Applications for multi-factor authentication using biometrics are becoming increasingly popular today. However, the Royal Thai Air Force has not implemented biometric technologies for identity verification. For this reason, the research team conducted a study and created a body of knowledge on the use of biometric technologies to identify individuals by their voice. The researchers created a model based on the LibriSpeech dataset and tested it using the Thai voice, as such biometric methods are more accurate, secure, and cost-effective than other biometric methods. The results reveal that environmental elements such as different sentence forms for verification and different types of recording devices are found to significantly affect the performance of the model. In contrast, wearing a mask and other quiet noises do not significantly decrease the performance of the model. Finally, the results also show the model’s vulnerability to deep voice spoofing, highlighting the need to develop a model that is resistant to such cyberattacks before it is used in the future.